ANALISIS PATH PADA INSENTIF, KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KOMITMEN ORGANISASIONAL - Helmy Adisaksana (Politeknik Negeri Malang, 2017)
The aim of this research is to know the description about work training, incentive, work satisfaction, and organizational commitment variable and also to know the influence between those variables in PT. Bank Rakyat Indonesia (Persero) Tbk. in the Branch Office of Malang Martadinata. This research takes sample for 52 people/respondents, in which all of them are employee in BRI Bank. Data collection conducted by questionnaire that published to all employees. Research method that used in this research was quantitaive research with descriptive format and be analyzed by using path analysis Research result shows that: 1) incentive variable influenced significantly to the work satisfaction; 2) incentive variable influenced significantly to the organizational commitment; 3) work satisfaction influenced significantly to the organizational commitment.